THE CAPABILITY OF ENGLISH DEPARTMENT STUDENTS OF FKIP UMSU IN PRONOUNCING THE DOUBLE “O” LETTERS BASED ON THE IPA ARE STILL POOR ENOUNGH - Amran, Ali -; Saragih, Mandra (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
This research study aims to investigate and analyse why English department students of FKIP UMSU are not standard enough in pronouncing the double “O” letters based on the standard of IPA (International Pronunciation Association). Pronunciation, according to Webster’s New World College Dictionary, 3rd Edition says, 1. The act or manner in pronouncing syllables, words, and phrases with regard to the production of sounds and the placing of stress, intonation etc, 2. a). Any of accepted or standard ways of pronouncing a word, etc, b). the transcription is symbol of such a way of pronouncing a word. Based on this information we can say that the pronunciations among languages are not always similar. The word /p-u-t/ as a verb in English means to drop something in a certain place while the word /p-u-t/ as a noun in Gayonese, means someone’s butt or ass. They both have the same pronunciation, but they carry different meanings. Let alone in English, say for example, the word /w-i-n-d/, even the spelling and the pronunciation is the same but they may have different words functions meanings. The noun /w-i-n-d/ means as air in motion, while the verb /w-i-n-d/ means to turn or make revolve. This research is focusing on the pronunciation of the “O-O” letters. In fact, not all “O-O” letters in English are pronounced similarly. The words; book, good, look, cook are pronounced similar, that is by using /u/, while the words: mood, moon, shoot, food, too, booth have different pronunciations, long /u:/ is applied. Then, the words; blood, flood is pronounced as /a/, door, floor, poor, is pronounced as /o/.The question is how standard can those English department students in semester III of FKIP UMSU pronounce those double “O-O” letters ? How many presents can they pronounce these double “O” letters correctly? And what causes them?